Dominica : Staff Report for the 2001 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Output and employment growth have been sluggish for the past several years, reflecting a difficult restructuring process associated with the retrenchment of the banana industry and the low productivity of public investment. The public finances have deteriorated in recent years as capital expenditure has increased sharply, while saving has been declining and foreign grants have fallen from their levels of the mid-1990s. Executive Directors emphasized the need for strong fiscal consolidation, and noted that generating higher public saving is the key to improve Dominica's growth prospects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet